14y-78y=10-45

Simplify each term.

Combine 14 and y.

y4-78y=10-45

Combine y and 78.

y4-y⋅78=10-45

Move 7 to the left of y.

y4-7y8=10-45

y4-7y8=10-45

To write y4 as a fraction with a common denominator, multiply by 22.

y4⋅22-7y8=10-45

Write each expression with a common denominator of 8, by multiplying each by an appropriate factor of 1.

Multiply y4 and 22.

y⋅24⋅2-7y8=10-45

Multiply 4 by 2.

y⋅28-7y8=10-45

y⋅28-7y8=10-45

Combine the numerators over the common denominator.

y⋅2-7y8=10-45

Simplify the numerator.

Move 2 to the left of y.

2⋅y-7y8=10-45

Subtract 7y from 2y.

-5y8=10-45

-5y8=10-45

Move the negative in front of the fraction.

-5y8=10-45

-5y8=10-45

Subtract 45 from 10.

-5y8=-35

Multiply both sides of the equation by -85.

-85⋅(-5y8)=-85⋅-35

Simplify -85⋅(-5y8).

Cancel the common factor of 8.

Move the leading negative in -85 into the numerator.

-85⋅(-5y8)=-85⋅-35

Move the leading negative in -5y8 into the numerator.

-85⋅-5y8=-85⋅-35

Factor 8 out of -8.

8(-1)5⋅-5y8=-85⋅-35

Cancel the common factor.

8⋅-15⋅-5y8=-85⋅-35

Rewrite the expression.

-15⋅(-5y)=-85⋅-35

-15⋅(-5y)=-85⋅-35

Cancel the common factor of 5.

Factor 5 out of -5y.

-15⋅(5(-y))=-85⋅-35

Cancel the common factor.

-15⋅(5(-y))=-85⋅-35

Rewrite the expression.

-1⋅(-y)=-85⋅-35

-1⋅(-y)=-85⋅-35

Multiply.

Multiply -1 by -1.

1⋅y=-85⋅-35

Multiply y by 1.

y=-85⋅-35

y=-85⋅-35

y=-85⋅-35

Simplify -85⋅-35.

Cancel the common factor of 5.

Move the leading negative in -85 into the numerator.

y=-85⋅-35

Factor 5 out of -35.

y=-85⋅(5(-7))

Cancel the common factor.

y=-85⋅(5⋅-7)

Rewrite the expression.

y=-8⋅-7

y=-8⋅-7

Multiply -8 by -7.

y=56

y=56

y=56

Solve for y 1/4y-7/8y=10-45